Open Fractures from Gustilo and Anderson to the Present: A Bibliometric Analysis with Global Productivity and Research Trends - Alıç, Taner; Hassa, Ercan (Indian journal of orthopaedics, 2022)
Background/Objective Despite the increase in global research on open fractures, which continue to be a significant cause of morbidity and mortality, seriously affecting the health and quality of life of patients, there has not been any bibliometric research on this subject. The aim of this study was to make a holistic analysis of scientific articles published on the subject of open fractures using bibliometric methods. Methods Articles published on the subject of open fractures between 1980 and 2021 were downloaded from the Web of Science (WoS) database, and were analysed using various statistical methods. Network visualisation maps were used to determine international collaborations and trend topics, and citation analyses to determine the most effective studies. Spearman’s correlation coefficient was used to determine correlations, and exponential smoothing predictors to estimate the number of articles to be published in the next 5 years. Results A total of 1742 articles were analysed. The 3 countries making the greatest contribution to literature were the USA (591, 33.9%), UK (219, 12.5%) and Germany (132, 7.5%). The most active author was Bhandari M. ( n = 22). The 3 most productive institutions were determined to be the University of California System ( n = 57), University of Washington (31), and Harborview Medical Center (29). The most active journal was Injury ( n = 143). Conclusion According to the analysis applied to identify trend topics, the topics most studied in recent years were determined to be surgical site infection, orthoplastics, intramedullary nail, Masquelet technique, BOAST, bone healing, closed reduction, classification, outcomes, and lower limb.